Automotive regions in transition: Preparing for connected and automated vehicles. (August 2021) - Trippl, Michaela; Baumgartinger-Seiringer, Simon; Goracinova, Elena; Wolfe, David A
The advent of 'connected and automated vehicles' (C/AV) is posing substantial transformation challenges for traditional automotive regions across the world. This article seeks to examine both conceptually and empirically how automotive regions reconfigure their industrial and support structures to promote new path development in the C/AV field. Drawing on recent conceptual advances at the intersection of evolutionary economic geography and innovation system studies, we develop an analytical framework that casts light on how regional preconditions provide platforms for asset modification that underpin different routes of transformation. We distinguish between a reorientation route and an upgrading route. The framework is applied to a comparative analysis of industrial path development and system reconfiguration towards C/AV in two automotive regions, namely Ontario (Canada) and the Austrian automotive triangle.